Pioneers! O pioneers! - MacNeil, Robert (Sydney, NSW. : BBC Education & Training, 1986)
Shows the evolution of American English from the revolutionary war through the roaring twenties.
Copy available in DVD format.
Keywords: English language -- United States -- History; Americanisms -- History